Exante economic analysis of biological control of coconut mite in Benin - Oleke, J.M.; Manyong, Victor M.; Mignouna, Djana B.; Isinika, A.; Mutabazi, K.D.; Hanna, R.; Sabelis, M. (2013)
The coconut mite, Aceria guerreronis Keifer, has been identified as one of the pests that pose a threat to the coconut industry in Benin. The study presents the simulation results of the economic benefits of the biological control of coconut mites in Benin using a standard economic surplus model. In the least optimistic scenario, the economy would derive an overall net gain of US$155,213.40. Considered at a discount rate of 12% for the period 2008-2027, net present value was about $207,721, while the internal rates of return or break-even discount rates are high at 13.21%. It is therefore recommended that contemporaneous with the release of natural predators of the coconut mite, plans should be underway for improving research and extension services to coconut farmers in Benin.